REMOTE PRACTICAL ANATOMY CLASSES: NEW CHALLENGES AND DIRECTIONS FOR TUTORS - Kažoka, Dzintra; Pilmane, Māra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Human Anatomy tutors had to adapt to Covid-19 reality by restructuring their methods by teaching in spring – autumn in 2020 at the Department of Morphology. The aims of this study were to identify and understand the variety of solutions being utilized by tutors and to clarify new challenges and directions. The open-ended interviews were used to collect data from 15 Anatomy tutors. Thematic analysis, used to analyze the qualitative data, emphasized the tutors’ perceptions of remote practical anatomy classes’ efficiency. Tutors developed their action plans for online teaching and highlighted the preparation of new materials, adoption of new technologies and skills. Based on the results of the transition from face-to-face to online anatomy teaching, there were detected five thematic items that were related to tutors’ challenges. It was concluded that challenges that need to become a priority for tutors in online education concern mainly the special training courses, design of new models, video and/or online lectures, demonstration labs, practical classes, collegial contacts, technicians, IT-staff and colleagues support, consultation hours and communication. Future directions for tutors must be effective not only for increasing the quality of the Human Anatomy study process but also for the evolution of anatomy education.